(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2023)
This study aims to understand the effect of online reviews on consumer purchase behavior. Therefore, more than 400 Bigz shops’ online reviews were collected. Based on the Stimulus Organism Response (S-O-R) Model, this paper studies the influence on consumer purchase behavior according to online reviews of experience goods from a new perspective of consumer learning. The data were processed using Statistical software tools. The statistical results show that positive reviews, describing ratings, picture reviews, appended reviews, and cumulative reviews influence consumer purchase behavior. The moderate reviews, negative reviews, logistics ratings, and service ratings are not significant in the results.